A Single Center Experience of Kidney Transplantation From Donation After Circulatory Death From India. (August 2017) - Singh, Sarbpreet; Sharma, Ashish; Kenwar, Deepesh; Singh, Navdeep; DasGupta, Soham; Rathi, Manish; Kohli, H.S; Gupta, K.L; Minz, Mukut
Abstract : Introduction: Donation after circulatory death (DCD) is a well-accepted source of organs worldwide. However, DCD has never been attempted in India so far due to lack of clarity in the country's Transplantation Act. The present report describes the initial use of DCD organs in India and highlights its challenges. Methods: Between Feb 2011 to Feb 2017 out of 82 deceased organ donations at our hospital 9 were DCD donor. Four had cardiac arrest after first brain death certifying committee evaluation. Two had cardiac arrest after brain death certification. Two donors were refused brain death certification. One patient with terminal lung disease had cardiac arrest in ICU. After declaration of death, donors received 25000 units of heparin. Chest compressions were restarted in 7 donors to maintain circulation and ventilation continued till organ retrieval. In rest of two donors, CPR was discontinued and shifted to operation theatre. All donors underwent rapid cannulation, infusion of cold preservative solution during retrieval surgery. All recipients got ATG induction except one who received Simulect. All recipients got Tacrolimus, Mycophenolate and steroids. Results: Out of 18 kidneys retrieved from 9DCD donors, 15 were transplanted and three discarded. One recipient withdrew consent at an advanced stage. Kidneys from one donor could not be utilised due to high resistance during perfusion. All except one donor had head injury as cause of death. Recipient's mean age was 39.9 + 8.6 yrs, M: F 11:4. All recipients except two required dialysis in immediate postoperative period. Mean postop day one urine output was 2543.33 ml (Range 10-13200 ml). The best baseline creatinine achieved was 1.41 + 0.38 mg% after mean duration of 22 days. The kidneys from donors where CPR was not continued after death declaration fared poorly when compared to those where CPR was continued. One of these kidneys never functioned. The other recipient of the same donor also had suboptimal function with lowest creatinine of 2.0 mg%. Both the kidneys from other donor where CPR was withheld showed evidence of patchy cortical necrosis (upto 25%) on protocol biopsies done at one week but these kidneys eventually regained normal renal function. The kidneys from donors where CPR was continued had earlier recovery of renal function. Conclusions: Kidneys from donors after cardiac arrest in an uncontrolled situation can serve as a useful adjunct in deceased donor programme. Continuing CPR after declaration of death seems to help in improving outcomes in these patients.